MODEL PENANGGULANGAN SEDIMENTASI DANAU BERBASIS MASYARAKAT DI PULAU BALI - I Made Nada; Ida Bagus Suryatmaja; I Gusti Ngurah Alit Wiswasta (Bumi Lestari Journal of Environment, 2017)
Countermeasures of community-based lake sediments are directed at maintaining the dynamic balance of Lake Batur, Beratan Lake, Lake Buyan and Lake Tamblingan. Sedimentation process of this lake is triggered by the pattern of management of agricultural land on the edge of the lake is less attention to aspects of soil and water conservation. The purpose of this research is; (1) to obtain a community-based sedimentation prevention model, (2) Mapping Land management on the edge of the lake, (3) erosion control strategy at the edge of the lake. This research is field experiment and surpei research, sampling is done by purposive sampling at Batur Lake 20 samples, Beratan Lake 16 samples, Lake Buyan 16 samples and Danau Tamblingan 12 Sampel. The socio-economic support data of the community was determined by 180 respondents in cluster sampling. Interviews and questionnaires are closed questions on a conventional scale. Characteristics of the lake were analyzed descriptive statistics using SPSS analysis tool. Land mapping is done by GPS method with GIS device. Predict erosion using the Universal Soil Loss Equation (USLE) Model while for sedimentation using the Stanford Sediment model. Data analysis to find out the model of development of sedimentation rate in lake due to erosion that happened, done by non linear regreresi analysis. The results of the analysis are tested on both sides with 95% confidence level on sediment data that is modeled whether or not significant effect